APLIKATIF PENDIDIKAN KARAKTER DALAM MENGATASI DEGRADASI MORAL DI SMPTK SOLA GRACIA ARASTAMAR RANTEBALLA - Agresia, Dewita; Ena (Jurnal PKM Setiadharma, 2024)
This service activity was held at SMPTK Sola Gracia Arastamar in Ranta Bella Village, Latimojong District, Luwu Regency, South Sulawesi. The PkM was held because many students at SMPTK Sola Gracia were experiencing moral degradation, such as being impolite, liking to curse, stealing and neglecting spiritual activities. This activity answers this problem by conducting education on applicable character education topics based on Christian religious values. The methods used are observation, two-way discussion, and library research. The results showed that SMPTK students who experienced problems after participating in PkM activities showed a behavioural transformation following moral values and Biblical principles. This activity will continue in the advanced monitoring stage, where the PkM team will control the students so that the activities carried out provide satisfactory and sustainable results.